The pattern of the NOS isoforms expression in arcuate nucleus of hypothalamus in experimental hypertension - Yu. M. Kolesnyk; O. V. Gancheva; S. V. Tishchenko (Zaporozhye State Medical University, 2017)
Abstract In is known, that one of the main regulators of the blood pressure (BP) is hypothalamus. The efficiency of the BP regulation in a changeable environment is dependable on its coherence and coordination. This intrahypothalamic coordinator is an arcuate nucleus. One of the main conditions of the proper neuronal function is combination of their functional stability and plasticity, which is strictly dependable on adequate blood supply, metabolic and trophic processes. One of the key regulators of the above mentioned features is nitric oxide (NO). The purpose was to establish the pathogenetic link of NO synthases isoforms imbalance in Arc of hypothalamus with formation of hypertension in etiologically different models of essential hypertension (SHR) and endocrine-saline model (ESM). Materials and methods. Study was conducted on 48 mature male rats with weight of 250-270 gram and age of 13-14 months, which were allocated into 3 experimental groups of 16 animals: the 1st group was control with Wistar rats; the 2nd group comprised of Wistar rats with ESM and the 3rd was made of SHR. Results. Formation of the hypertension in ESM and SHR rats led to similar changes of the pattern of NOS isoforms expression. We found the significant increase of the IRM content to nNOS and iNOS, but decrease to eNOS. In the same time, the constitutive isoforms concentration (nNOS and eNOS) was significantly lower compared with control group, and iNOS concentration in both groups with hypertension was higher than in control group (6 % and 9 %, p < 0.05, respectively). Conclusions: In rats with normal BP in Arc, the most expressed NOS isoform was the endothelial one. We found the typical changes in the pattern of the NOS isoforms allocation. We also found the increase of the content of all isoforms with the decrease of the concentration of constitutional ones (nNOS and eNOS), but the increase of the iNOS concentration.